NEGARA ISLAM DEMOKRASI SAMPAI OTOKRASI - Meifa Adinda Erwina; Erman Erman; Radhiatul Hasnah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research aims to analyze the factors influencing the transformation of governance systems in majority-Muslim countries, focusing on the relationship between history, religion, and socio-political contexts in shaping the diverse governance systems. The political dynamics in majority-Muslim countries reflect the variety of governance systems influenced by historical, religious, cultural, and geopolitical factors. Some countries like Indonesia, Tunisia, and Senegal have successfully built full or transitional democracies, enabling active public participation in decision-making processes. In contrast, countries like Saudi Arabia and the United Arab Emirates maintain autocratic structures based on Sharia law as the basis of legitimacy. The method used is qualitative research with a library research approach, where various sources of information such as books, academic journals, and official reports are reviewed to understand the differences in governance systems from democracy to autocracy. The results of the study show that, despite the diversity in the application of governance systems, many Muslim-majority countries are striving to manage power while responding to social, economic, and public needs, either through fair elections or socio-economic reforms. This research is expected to provide insights into the challenges and opportunities in the journey towards stable and inclusive governance in majority-Muslim countries.